KEGIATAN PENGELOLA TAMAN BACAAN MASYARAKAT SAHABAT PENA DALAM LAYANAN INFORMASI SAAT PANDEMI COVID-19 - Tita Nursari (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2021)
The Covid-19 pandemic has greatly affected every area of public life, including the role of information managers in the information service process. The Information Manager made various efforts to provide information services during a pandemic, one of which was by the manager of the Sahabat Pena Community Library (TBM). This study aims to determine the role of the Sahabat Pena Community Library manager, the programs being carried out, and the parties working together in providing information services to the community. The method used is to conduct a literature review, observation, and online interviews with the community Library managers. The results of the study show that the role of the Sahabat Pena Community Library is to become an educator and field activist. Programs carried out in the information service effort are Jumat Berkah, Peduli Lansia, Donasi Buku, and Diskusi Aktifis Group. Information services are carried out directly by still paying attention to health protocols and online by utilizing social media. And in collaboration with the Karang Taruna and the Komite Nasional Pemuda Indonesia (KNPI) Gununghalu District in an effort to accelerate and facilitate the implementation of the program being carried out.Keyword: Information services, the role of information manager, Sahabat Pena community library